Integrating Multicultural Education into Primary School Curricula in Southeast Asia: A Comparative Analysis of Indonesia, Malaysia, Thailand, and the Philippines - Chakrabhand , Chakrabhand (PERFECT EDUCATION FAIRY, 2025)
Southeast Asia is one of the world’s most culturally diverse regions, encompassing multiple ethnic, linguistic, and religious groups. This diversity underscores the importance of embedding multicultural values in education to foster social cohesion and tolerance from an early age. This study employs a qualitative literature review to analyze how multicultural education is integrated into primary school curricula in Indonesia, Malaysia, Thailand, and the Philippines. Findings indicate that while each nation has developed unique approaches, commonalities exist in the inclusion of multicultural principles within citizenship, language, and social studies subjects. Indonesia emphasizes Pancasila values, Malaysia promotes ethnic harmony through civic and moral education, Thailand stresses social stability and nationalism, and the Philippines prioritizes indigenous rights through the Indigenous Peoples Education (IPEd) program. Challenges include political differences, cultural majoritarianism, and limited acceptance of diversity issues. However, best practices—such as the Pancasila Student Profile in Indonesia and the IPEd program in the Philippines—serve as exemplary models for fostering inclusive and tolerant learning environments. The study concludes that developing regionally integrated multicultural education frameworks could enhance intercultural competence and strengthen ASEAN identity among young learners.